2020
DOI: 10.1080/02602938.2020.1748569
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ perceptions of responsibility-sharing in feedback processes

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…Winstone, Pitt, and Nash ( 2021 ), for example, have looked at understanding how lectures saw their role in assessment and feedback; they compared two models of feedback, one oriented in a cognitivist approach which emphasises the responsibility in the lecturer and another one following a socio-constructivist approach which brings into the foreground responsibilities in the feedback process to the student. In their research, they found that the majority of lecturers were influenced by transmission-based models of feedback with lecturers conveying greater certainty in these types of assessment practices and ‘were more likely to use referents to power and positive emotion, when describing their own as opposed to students’ responsibilities’ (Winstone et al, 2021 , p. 118). This dominant role is often ill-defined as it is implicit in centuries of tradition particularly when we discuss assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Winstone, Pitt, and Nash ( 2021 ), for example, have looked at understanding how lectures saw their role in assessment and feedback; they compared two models of feedback, one oriented in a cognitivist approach which emphasises the responsibility in the lecturer and another one following a socio-constructivist approach which brings into the foreground responsibilities in the feedback process to the student. In their research, they found that the majority of lecturers were influenced by transmission-based models of feedback with lecturers conveying greater certainty in these types of assessment practices and ‘were more likely to use referents to power and positive emotion, when describing their own as opposed to students’ responsibilities’ (Winstone et al, 2021 , p. 118). This dominant role is often ill-defined as it is implicit in centuries of tradition particularly when we discuss assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These concepts are enacted through disciplinary feedback practices that are facilitated when educators establish learning cultures which enable their productive implementation. Within these learning cultures shared responsibilities in the development of feedback literacy are posited as essential: educators design opportunities for students to involve themselves in feedback exchanges, whereas students carry responsibilities to engage with and use feedback (Carless and Winstone 2020;Winstone, Pitt, and Nash 2021). Shulman's Shulman (2005) concept of signature pedagogies informs the framing of signature feedback practices.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In addition, there may be potential for the FQI to be adapted for other contexts, such as higher education, to support a socio-constructivist feedback paradigm that focuses on educators and learners collaborating together [25,26,32].…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…It may be that, in the absence of alternative strategies, educators are simply repeating feedback rituals they experienced as students or using formulaic assessment rubrics, which are not designed with an interactive process in mind. Hence there is a need for new schemas that are structured to promote educator and learner collaboration during feedback interactions [24][25][26].…”
Section: Introductionmentioning
confidence: 99%